Gambaran Kejadian Efek Samping Kemoterapi Pasien Kanker Payudara Yang Menggunakan M-Health App “Pantau Kanker” Di Rumah Sakit Kota Yogyakarta - Nur P, Kanindya; Zukhruf Saputri, Ginanjar; Supadmi, Woro; Akrom, Akrom; Muhlis, Muh (Universitas Bhakti Kencana, 2024)
Breast cancer is a type of cancer with a fairly high death rate. DIY Province has the highest prevalence of breast cancer in Indonesia. One of the medical ways to treat cancer is chemotherapy which uses cytostatic drugs, aimed at killing or slowing the growth of cancer cells. However, these drugs cause side effects in patients. Education is needed in dealing with side effects in order to monitor the patient's condition. Therefore, this research was conducted to determine the incidence of side effects of chemotherapy in breast cancer patients who use the M-Health app